Manajemen Risiko Usahatani Cabai Rawit: Studi Kasus Di Kawasan Gunung Merapi (Forum Agribisnis, 2024)
Cayenne pepper (Capsicum frutescens L) is a common horticultural commodity cultivated by farmers in the Mount Merapi area. Farmers in this region face the risk of fluctuating productivity due to unpredictable volcanic eruption activities. This study aims to describe the types, sources, and levels of risk, analyze and examine risk management in bird's eye chili farming based on risk levels, risk mapping, and the total household income analysis of bird's eye chili farmers in Mount Merapi. The sample consists of 100 farmers selected through simple random sampling, with the criteria being residents who have been farming cayenne pepper for 10 years in the Mount Merapi area, growing cayenne pepper as the main commodity on their farmland, and farmers with and without additional income sources outside of farming. Data analysis includes risk analysis, total household income analysis, and descriptive quantitative analysis. In Pakem Subdistrict, the coefficient of variation values for production, price, and profit risks are 0.67, 0.08, and 1.20, respectively. In Dukun Subdistrict, these values are 0.55, 0.14, and 2.40, respectively. Lastly, in Selo Subdistrict, the values are 0.45, 0.07, and 0.84, respectively. Household income analysis is divided into two categories: farmers with additional income sources outside of farming and those without additional income sources in each district. The highest average total household income of cayenne pepper farmers is found in Selo Subdistrict. Important considerations in agricultural risk management include providing insurance for cayenne pepperi, market development, and land diversification.